Respuesta :
[tex](6m\pm7)^2=(6m)^2\pm2\cdot6m\cdot7+7^2=\boxed{36m^2\pm84m+49}\\\\Use:(a\pm b)^2=a^2\pm2ab+b^2[/tex]
Answer:
Option a [tex](6m+ 7)^2=36m^2+49+84m[/tex]
Option d [tex](6m- 7)^2=36m^2+49-84m[/tex]
Step-by-step explanation:
Given : Expression - [tex](6m\pm7)^2[/tex]
To find : The square of the given expression
Solution :
We have to solve [tex](6m\pm7)^2[/tex]
Apply property : [tex](a\pm b)^2=a^2+b^2\pm 2ab[/tex]
In the given expression [tex](6m\pm 7)^2[/tex]
a=6m, b=7
The solution is
[tex](6m+7)^2=(6m)^2+(7)^2\pm 2(6m)(7)[/tex]
[tex](6m+7)^2=36m^2+49\pm 84m[/tex]
Therefore,
If the sign is '+' then Option a is correct.
If the sign is '-' then Option d is correct.